2018
DOI: 10.1021/acs.jpcc.8b06089
|View full text |Cite
|
Sign up to set email alerts
|

NMR-Detected Dynamics of Sodium Co-Intercalation with Diglyme Solvent Molecules in Graphite Anodes Linked to Prolonged Cycling

Abstract: Following the success of Li-ion batteries, Naion batteries are becoming an important economical alternative, particularly where weight and density considerations are not of primary importance. Graphite, the anode of choice for nearly all commercial Li-ion battery applications, has only recently been successfully used as such in Na systems. This unprecedented success was due to the proper choice of solvent, e.g., diglyme. Interestingly, lithium performs poorly under such conditions, which is the converse of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 58 publications
9
32
2
Order By: Relevance
“…The high rate capability has been rationalized by NMR measurements and theory. A diffusion coefficient of D Na + = 1.1 × 10 –8 cm 2 s –1 was determined by Jung et al, which is almost one order of magnitude larger than the diffusion coefficient of Li + in LiC 6 . …”
Section: Introductionmentioning
confidence: 88%
“…The high rate capability has been rationalized by NMR measurements and theory. A diffusion coefficient of D Na + = 1.1 × 10 –8 cm 2 s –1 was determined by Jung et al, which is almost one order of magnitude larger than the diffusion coefficient of Li + in LiC 6 . …”
Section: Introductionmentioning
confidence: 88%
“…This explains why NIBs using this compound can be charged and discharged at a high rate. The diglyme coordinating to Na in the graphite layers was also analyzed by high‐resolution 1 H and 13 C NMR [46] . Cross‐polarization (CP) dynamic measurements demonstrated that the Na‐(diglyme) 2 complex is weak when interacting with the graphene sheets, as compared to Li‐(diglyme) 2 .…”
Section: Anode (Negative Electrode) Materialsmentioning
confidence: 99%
“…13 C NMR spectroscopy has been applied to study intercalation mechanisms of alkali-metal ions into different types of graphitic carbon. A graphite peak at 123 ppm was found in the samples discharged with diglyme electrolyte, which allowed efficient cointercalation of Li or Na ions into graphite, whereas no apparent 13 C signal from uncycled graphite (with 13 C natural abundance) was observed . The single-pulse spectrum on an expanded scale however exhibited a very broad resonance at 89 ppm.…”
Section: Introductionmentioning
confidence: 99%